(3GdQGeRI GdcGajI aj Ydei GdYQhV hGdbGajIs - (3GdNRQLj , VjGA GdOjf CHh eMeO YHO Gddg Hf eMeO GdNRQLj,J (B626 (3g` s ((3eQJVi Hf eUWai Hf MSf GdcQOi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg KbJi GdMeO ddg hMOg hUdGJg hSdGeg Ydi ef dGfHi HYOg , bGd GdTjN VjGA GdOjf CHh eMeO YHO Gddg GdNRQLi hddTYQ ejRGf JSei YQhVg HgG GdfbU hGdQLMGf jOQjgeG GdaJi s
(3BNQgG (B:s
(3hbO cedJ SJkG hJSYjf aGdPi JhSW ai PG GdYde JhSYg MHkG hjSCd YHO Gddg PG GdNRQLi ef eWGdYgG EJMGag efg HGdOYG hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde Bejf s
(3HgG fXGe GdJYbjHIs
(3HChdgG hbajI HGSe eMeO SYjO Hf eMeO Hc EjGS GdOeTbis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B124 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B117 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B460s
Keywords: (3GdYQhV hGdbhGais